A MORPHOSEMANTIC STUDY OF TOPONYM WITH PREFIX ‘CI’ IN SUNDANESE ETHNIC – INDONESIA - Ujang Komara; Cece Sobarna; Gugun Gunardi; Ahman Sya (UIBU, 2019)
The study highlights the morphosemantic analysis (morphological classification and semantic category) of toponym with prefix ‘ci’ in Sundanese ethnic of West Java-Indonesia. The results of analysis are used as substantive sources to describe the former local wisdom values reflected on the social and cultural paradigm, such as norms, ethics, people’s mental capacity, and local traditions. The study also attempts to examine the contemporary evidence of values in the community to ensure its sustainability. The research methodology uses a descriptive qualitative by collecting the data with field observation, depth-interview, and documents. It contributes to the debates of rethinking the agenda of political toponymy stated by Reuben Rose-Redwood. The findings indicate that the morphological classification of Cikalong toponym includes a derivative form referring to a poly-morphemic word. The denotative meaning of toponym includes a complex category that reflects the complex ways of thinking in naming the place. Toponym is contemporary signified by the destructions of local wisdom values due to the incoming new social and cultural shapes. It offfers some arguments for the preservation process.